2021
DOI: 10.3390/genes12020182
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA HOXA11-AS and Transcription Factor HOXB13 Modulate the Expression of Bone Metastasis-Related Genes in Prostate Cancer

Abstract: Long noncoding RNAs (lncRNAs) are emerging as critical regulators of gene expression, which play fundamental roles in cancer development. In this study, we found that homeobox A11 antisense RNA (HOXA11-AS), a highly expressed lncRNA in cell lines derived from prostate cancer bone metastases, promoted the cell invasion and proliferation of PC3 prostate cancer cells. Transcription factor homeobox B13 (HOXB13) was identified as an upstream regulator of HOXA11-AS.HOXA11-AS regulated bone metastasis-associated C-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Homeobox (HOX) A11 antisense lncRNA (HOXA11-AS), a highly conserved lncRNA [ 11 ], has been reported to be associated with the drug resistance of different cancers. For example, HOXA11-AS enhanced CDDP resistance of human lung adenocarcinoma cells via regulating miR-454-3p/Stat3 axis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Homeobox (HOX) A11 antisense lncRNA (HOXA11-AS), a highly conserved lncRNA [ 11 ], has been reported to be associated with the drug resistance of different cancers. For example, HOXA11-AS enhanced CDDP resistance of human lung adenocarcinoma cells via regulating miR-454-3p/Stat3 axis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, based on mechanistic studies, it becomes apparent that the majority of HOX genes have an oncogenic function. Most HOX genes, including HOXB7, 15‐47 HOXB8 48‐54 and HOXC10 55‐72 are only reported to have oncogenic functions, while only two, HOXA5 73‐83 and HOXB13, 84‐108 are notable for having oncogenic functions reported in around 50% of publications, and tumour suppressor functions in the other 50%. Only one HOX gene, HOXD10, seems to act almost exclusively as a tumour suppressor, albeit with a notable exception in head and neck squamous cell carcinoma (HNSCC) 109‐121 …”
Section: Oncogenic Vs Tumour Suppressor Functions Of Hox Genesmentioning
confidence: 99%
“…In studies where HOXB13 is identified as promoting oncogenesis, it is frequently because it has a role in driving metastasis. In prostate cancer, this is through increasing the expression of integrin subunits (ITGAV and ITGB1) specific to prostate cancer bone metastasis, 96 by preventing the expression of prostate‐derived Ets factor (PDEF) which inhibits metastasis, 90 through blocking the transport of zinc ions which in turn increases NF‐κB‐mediated signalling by reducing inhibitor of NF‐κB alpha (IκBα) activity, 92 and by promoting expression of the epithelial to mesenchymal transition (EMT)‐inducing Slug transcription factor 105 . Conversely, tumour‐suppressor functions of HOXB13 in prostate cancer seem to depend on its ability to block cell division through the downregulation of cyclin D1 through competition for TCF4 binding to its promoter, 87,88 and androgen signalling through direct interaction with the androgen receptor 89,122 .…”
Section: Oncogenic Vs Tumour Suppressor Functions Of Hox Genesmentioning
confidence: 99%
“…The lncRNA transcription factor homeobox B13 (HOXB13) has been identified as an upstream regulator of bone metastasis-related signals in prostate cancer. HOXB13 promotes the bone metastasis of metastatic prostate cancer by regulating the production of CCL2/CCR2 cytokines and integrin signals in an autocrine and paracrine manner [ 11 ].…”
Section: Introductionmentioning
confidence: 99%